Nonaqueous electrolyte electricity storage element
By using a positive electrode active material containing tungsten elements and setting an appropriate amount of negative electrode active material layer in the nonaqueous electrolyte power storage element, the problem of lowering input power in a high-temperature environment is solved, and the input maintenance rate in a high-temperature environment is improved.
Patent Information
- Application Number
- CN202380041445.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2023-05-17
- Publication Date
- 2025-01-17
AI Technical Summary
The input power of the existing nonaqueous electrolyte power storage components is easily reduced in a high temperature environment, and it is difficult to maintain the initial input level.
By containing tungsten elements in the positive electrode active material layer, and setting the mass per unit area of 3.8 mg/cm2 to 4.8 mg/cm2 and an average thickness of 30 μm or more on the negative electrode active material layer, the precipitation of tungsten elements is restricted and the negative electrode is reduced The resistance becomes larger, which increases the input maintenance rate.
The initial input of the nonaqueous electrolyte storage element in a high temperature environment is achieved and the input maintenance rate is high, ensuring the stable performance of the equipment under high temperature conditions.
Smart Images

Figure CN119325662A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a nonaqueous electrolyte storage element. Background Art
[0002] Non-aqueous electrolyte secondary batteries represented by lithium ion secondary batteries are mostly used in electronic devices such as personal computers, communication terminals, and automobiles due to their high energy density. Non-aqueous electrolyte secondary batteries are generally composed of a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte between the electrodes, and are charged and discharged by performing charge transfer ions between the two electrodes. In addition, as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and double electric layer capacitors have also been widely popularized.
[0003] The positive electrode active material for non-aqueous electrolyte storage element uses lithium transition metal composite oxides, polyanion compounds, etc. In order to improve the performance of non-aqueous electrolyte storage element, the surface of the particles of positive electrode active material is also coated with other compounds. Patent document 1 records the positive electrode material for lithium secondary battery formed by coating the surface of particles of lithium manganese composite oxide with metal oxides such as titanium oxide and tin oxide.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2001-6676 Summary of the invention
[0007] For non-aqueous electrolyte storage elements, it is desirable that the initial input is large, and that the input is not easily reduced even after storage in a high temperature environment. It should be noted that input refers to the energy (power: W) that the non-aqueous electrolyte storage element can absorb per unit time during charging. In other words, input refers to the input power during charging.
[0008] An object of the present invention is to provide a non-aqueous electrolyte storage element having a large initial input and a high input retention rate after storage in a high-temperature environment.
[0009] A nonaqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material containing a tungsten element, and the mass per unit area of the negative electrode active material layer is 3.8 mg / cm 2 ~4.8mg / cm 2 , the average thickness of the negative electrode active material layer is greater than 30 μm.
[0010] According to one aspect of the present invention, it is possible to provide a nonaqueous electrolyte power storage element having a large initial input and a high input retention rate after storage in a high-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a perspective view showing one embodiment of a non-aqueous electrolyte electricity storage element.
[0012] Figure 2 This is a schematic diagram showing one embodiment of an electricity storage device including a plurality of nonaqueous electrolyte electricity storage elements assembled together. DETAILED DESCRIPTION
[0013] First, the outline of the nonaqueous electrolyte energy storage device disclosed in this specification will be described.
[0014] [1]: A non-aqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material containing a tungsten element, and the mass per unit area of the negative electrode active material layer is 3.8 mg / cm 2 ~4.8mg / cm 2 , the average thickness of the negative electrode active material layer is greater than 30 μm.
[0015] The nonaqueous electrolyte storage element described in [1] above has a large initial input and a high input maintenance rate after storage in a high temperature environment. The reason is still uncertain, but it is speculated to be the following. By using a positive electrode active material containing tungsten, the resistance of the positive electrode becomes smaller and the initial input of the nonaqueous electrolyte storage element becomes larger. However, when the nonaqueous electrolyte storage element is stored in a high temperature environment, the tungsten element contained in the positive electrode active material dissolves into the nonaqueous electrolyte. The dissolved tungsten element precipitates on the negative electrode, which becomes the cause of the increase in the resistance of the negative electrode. As a result, the input of the nonaqueous electrolyte storage element is reduced. In addition, the dissolved tungsten element is more likely to precipitate on the surface side of the negative electrode active material layer. Here, when the mass per unit area of the negative electrode active material layer is small and the negative electrode active material layer is thin, the negative electrode active material layer as a whole is easily affected by the precipitation of the tungsten element, and the resistance of the negative electrode becomes larger. Therefore, by increasing the mass per unit area of the negative electrode active material layer and thickening the negative electrode active material layer, the influence of the precipitation of the tungsten element in the negative electrode active material layer is limited to the surface side, which can suppress the increase in the resistance of the negative electrode. However, when the mass per unit area of the negative electrode active material layer is too large, the thickness of the tungsten element precipitation layer per unit area on the surface side of the negative electrode active material layer becomes too thick, which hinders the movement of charge transport ions, so the resistance of the negative electrode after storage in a high temperature environment becomes large. In the non-aqueous electrolyte storage element described in [1] above, the mass per unit area of the negative electrode active material layer is 3.8 mg / cm 2~4.8mg / cm 2 The average thickness of the negative electrode active material layer is 30 μm or more, so it is estimated that the increase in resistance of the negative electrode after storage in a high temperature environment is suppressed, and the input retention rate is high.
[0016] As described later, according to the research conducted by the present inventors, it was confirmed that the mass per unit area of the negative electrode active material layer was set to 3.8 mg / cm 2 ~4.8mg / cm 2 As for the improvement of input maintenance rate brought about by the range of, the same tendency is not shown when using the positive electrode active material without tungsten element. Therefore, by setting the mass per unit area of the above-mentioned negative electrode active material layer within a specific range and combining it with the positive electrode active material containing tungsten element, as a specific effect produced by the combination, a non-aqueous electrolyte storage element with a significantly improved input maintenance rate after storage in a high temperature environment can be provided.
[0017] “The mass per unit area of the negative electrode active material layer” and “the average thickness of the negative electrode active material layer” refer to the mass per unit area of one negative electrode active material layer and the average thickness of one negative electrode active material layer. For example, when the negative electrode has a negative electrode substrate and negative electrode active material layers are provided on both sides of the negative electrode substrate, “the mass per unit area of the negative electrode active material layer” and “the average thickness of the negative electrode active material layer” refer to the mass per unit area and the average thickness of the negative electrode active material layer on one side. In addition, the “average thickness” of the negative electrode active material layer refers to the average value of the thickness measured at any 10 points of the negative electrode active material layer.
[0018] [2]: In the non-aqueous electrolyte storage element described in [1] above, the ratio of the mass per unit area of the negative electrode active material layer to the mass per unit area of the tungsten element contained in the positive electrode active material layer may be 30 or more. Thus, when the mass per unit area of the negative electrode active material layer is sufficiently large relative to the mass per unit area of the tungsten element in the positive electrode active material layer, the influence of the precipitation of the tungsten element in the negative electrode active material layer is further limited to the surface side, and the amount of tungsten element per unit area of the negative electrode active material layer precipitated on the surface side of the negative electrode active material layer is also reduced, so that the input retention rate of the non-aqueous electrolyte storage element described in [2] after storage in a high temperature environment is further improved. "The mass per unit area of the tungsten element contained in the positive electrode active material layer" refers to the mass per unit area of the tungsten element contained in one positive electrode active material layer. For example, when the positive electrode has a positive electrode substrate and positive electrode active material layers are provided on both sides of the positive electrode substrate, "the mass per unit area of the tungsten element contained in the positive electrode active material layer" refers to the mass per unit area of the tungsten element contained in the positive electrode active material layer on one side.
[0019] [3]: In the non-aqueous electrolyte storage element described in [1] or [2] above, the porosity of the negative electrode active material layer may be 40% or more. In the non-aqueous electrolyte storage element described in [3] above, the porosity of the negative electrode active material layer is set to 40% or more, thereby further improving the input retention rate after storage in a high temperature environment.
[0020] The “porosity (%)” of the negative electrode active material layer is calculated by assuming that the apparent volume (including the volume of voids) of the negative electrode active material layer is V. 1 The sum of the actual volumes of the materials constituting the negative electrode active material layer is set to V 2 When (1-V 2 / V 1 The actual volume sum of the materials constituting the negative electrode active material layer V 2 It can be calculated from the content of each material in the negative electrode active material layer and the true density of each material.
[0021] A nonaqueous electrolyte storage element, a storage device, a method for manufacturing a nonaqueous electrolyte storage element, and other embodiments of the present invention are described in detail. It should be noted that the names of the components (components) used in each embodiment are sometimes different from the names of the components (components) used in the background art.
[0022] <Non-aqueous electrolyte energy storage device>
[0023] A nonaqueous electrolyte storage element (hereinafter also referred to as "storage element") of one embodiment of the present invention comprises: an electrode body having a positive electrode, a negative electrode and a separator, a nonaqueous electrolyte, and a container for accommodating the electrode body and the nonaqueous electrolyte. The electrode body is usually a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked via a separator, or a wound type in which a positive electrode and a negative electrode are wound in a state of being stacked via a separator. The nonaqueous electrolyte exists in a state of being immersed in the positive electrode, the negative electrode and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter also referred to as "secondary battery") is described.
[0024] (positive electrode)
[0025] The positive electrode includes a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.
[0026] The positive electrode substrate has electrical conductivity. Whether it has "electrical conductivity" is determined by measuring the volume resistivity of 10 7Ω·cm is used as the threshold value for determination. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among them, from the viewpoints of potential resistance, high conductivity and cost, aluminum or aluminum alloys are preferred. As the positive electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the viewpoint of cost, foil is preferred. Therefore, as the positive electrode substrate, aluminum foil or aluminum alloy foil is preferred. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H-4160 (2006) can be exemplified.
[0027] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate to the above range, the strength of the positive electrode substrate can be increased, and the energy density per unit volume of the secondary battery can be increased.
[0028] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer reduces the contact resistance between the positive electrode substrate and the positive electrode active material layer by including a conductive agent such as carbon particles. The composition of the intermediate layer is not particularly limited, and for example, includes a binder and a conductive agent.
[0029] The positive electrode active material layer contains a positive electrode active material and may contain any components such as a conductive agent, a binder (adhesive), a thickener, and a filler as necessary.
[0030] The positive electrode active material contains tungsten. The tungsten element can be in the form of oxide (WO 3) and other compounds. The compound containing the tungsten element, for example, covers at least a portion of the surface of particles of a substance capable of absorbing and releasing charge transport ions such as lithium ions. In other words, the positive electrode active material may include a substance capable of absorbing and releasing charge transport ions and a compound containing the tungsten element. The positive electrode active material may essentially consist only of a substance capable of absorbing and releasing charge transport ions and a compound containing the tungsten element. The substance capable of absorbing and releasing charge transport ions itself may contain the tungsten element. The tungsten element may, for example, exist on the surface of particles of the positive electrode active material. The tungsten element may also exist inside the particles of the positive electrode active material. By containing the tungsten element in this way, the side reactions of the positive electrode can be suppressed, the conductivity of charge transport ions such as lithium ions can be improved, and as a result, the input of the non-aqueous electrolyte storage element can be improved. As a form of containing the tungsten element in the positive electrode active material, there is a form in which a compound containing the tungsten element is coated on the surface of particles of a substance capable of absorbing and releasing charge transport ions. In addition, there is also a form in which a compound containing tungsten is carried on the particle surface of the positive electrode active material or included in the particle interior by adding tungsten when synthesizing a material that can occlude and release charge transport ions and firing. As the positive electrode active material containing tungsten, a commercially available product can be used.
[0031] As the material capable of absorbing and releasing charge transport ions, preferably, a material capable of absorbing and releasing lithium ions can be used, and conventionally known positive electrode materials can be used. Examples of such materials include α-NaFeO 2 A lithium transition metal composite oxide having a type crystal structure, a lithium transition metal composite oxide having a spinel type crystal structure, a polyanion compound, a chalcogen compound, sulfur, etc. 2 Lithium transition metal composite oxides with a crystal structure of the type include Li[Li x Ni (1-x) ]O 2 (0≤x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O 2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co (1-x) ]O 2 (0≤x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O 2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β)]O 2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O 2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β) etc. Examples of lithium transition metal composite oxides having a spinel crystal structure include Li x Mn 2 O 4 , Li x Ni γ Mn (2-γ) O 4 As polyanion compounds, LiFePO 4 、LiMnPO 4 、LiNiPO 4 、LiCoPO 4 , Li 3 V 2 (PO 4 ) 3 , Li 2 MnSiO 4 , Li 2 CoPO 4 F, etc. As chalcogen compounds, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be cited. A part of the atoms or polyanions in these materials can also be replaced by atoms or anions formed by other elements. These materials can be used alone or in combination of two or more.
[0032] As the material capable of absorbing and releasing the charge transport ion, lithium transition metal composite oxides are preferred, and α-NaFeO 2 A lithium transition metal composite oxide with a crystal structure of the type, preferably Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O 2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β). The above Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O 2 For example, 0.1≤γ<0.9 and 0.1≤β<0.9 are preferable. When such a substance is used, the input improvement effect by the tungsten element can be fully exerted.
[0033] The positive electrode active material may further contain transition metal elements other than tungsten. When a lithium transition metal composite oxide, a polyanion compound, or the like is used as a material capable of absorbing and releasing charge transport ions, the positive electrode active material further contains transition metal elements other than tungsten. The content of tungsten in the positive electrode active material relative to transition metal elements other than tungsten is preferably 0.2 mol% to 3 mol%, and more preferably 0.5 mol% to 2 mol%. By making the content of tungsten above the lower limit, the effect of tungsten in the positive electrode active material is fully exerted, and the initial input becomes larger. On the other hand, by making the content of tungsten below the upper limit, the ion conductivity of the positive electrode active material is improved, resulting in a larger initial input.
[0034] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% to 99% by mass, more preferably 70% to 98% by mass, and further preferably 80% to 95% by mass. By making the content of the positive electrode active material within the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.
[0035] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably set to 0.1 μm to 20 μm, for example. By making the average particle size of the positive electrode active material above the above lower limit, the manufacture or handling of the positive electrode active material becomes easy. By making the average particle size of the positive electrode active material below the above upper limit, the electron conductivity of the positive electrode active material layer is improved. It should be noted that when a composite of the positive electrode active material and other materials is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. "Average particle size" refers to a dilution obtained by diluting the particles with a solvent in accordance with JIS-Z-8825 (2013), and the particle size distribution of the dilution is measured using a laser diffraction / scattering method. Based on the particle size distribution, the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%.
[0036] In order to obtain a powder with a predetermined particle size, a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, a method using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotating airflow jet mill, or a sieve can be cited. During pulverization, wet pulverization in which an organic solvent such as water or hexane coexists can also be used. As a classification method, a sieve, a pneumatic classifier, etc. are used together with a dry method or a wet method as needed.
[0037] The conductive agent is not particularly limited as long as it is a material with conductivity. As such a conductive agent, for example, carbonaceous materials, metals, conductive ceramics, etc. can be cited. As carbonaceous materials, graphite, non-graphite carbon, graphene-based carbon, etc. can be cited. As non-graphite carbon, carbon nanofibers, pitch-based carbon fibers, carbon black, etc. can be cited. As carbon black, furnace black, acetylene black, Ketjen black, etc. can be cited. As graphene-based carbon, graphene, carbon nanotubes (CNT), fullerene, etc. can be cited. As the shape of the conductive agent, powder, fiber, etc. can be cited. As the conductive agent, one of these materials can be used alone, or two or more can be mixed and used. In addition, these materials can also be composited and used. For example, a material composited with carbon black and CNT can be used. Among them, based on the viewpoint of electronic conductivity and coating properties, carbon black is preferred, and acetylene black is preferred.
[0038] The content of the conductive agent in the positive electrode active material layer is preferably 1% to 10% by mass, and more preferably 3% to 9% by mass. When the content of the conductive agent is within the above range, the energy density of the secondary battery can be increased.
[0039] Examples of adhesives include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, and polyimide; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.
[0040] The content of the binder in the positive electrode active material layer is preferably 0.5% by mass to 10% by mass, and more preferably 1% by mass to 9% by mass. When the content of the binder is within the above range, the active material can be stably retained.
[0041] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be inactivated in advance by methylation or the like.
[0042] The content of the thickener in the positive electrode active material layer may be, for example, 0.1% to 6% by mass, or 0.5% to 3% by mass. The content of the thickener in the positive electrode active material layer may be 1% by mass or less, or the positive electrode active material layer may not contain the thickener.
[0043] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, inorganic oxides such as barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.
[0044] The content of the filler in the positive electrode active material layer may be, for example, 0.1% to 8% by mass, or 0.5% to 5% by mass. The content of the filler in the positive electrode active material layer may be 3% by mass or less, or 1% by mass or less, or the positive electrode active material layer may not contain any filler.
[0045] The positive electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb as components other than the positive electrode active material, conductive agent, binder, thickener and filler.
[0046] The mass per unit area of the positive electrode active material layer is not particularly limited, but is, for example, 5.0 mg / cm 2 ~15mg / cm 2 The lower limit of the mass per unit area of the positive electrode active material layer is preferably 5.5 mg / cm 2 , more preferably 5.8 mg / cm 2 or 6.0mg / cm 2 In some embodiments, the mass per unit area of the positive electrode active material layer may be, for example, 6.5 mg / cm 2 Above, it can also be 7.0mg / cm 2 The upper limit of the mass per unit area of the positive electrode active material layer is preferably 12 mg / cm 2 , more preferably 10 mg / cm 2. In a non-aqueous electrolyte storage element having a positive electrode active material layer whose mass per unit area is within the above range, the application effect of the present configuration can be more suitably exerted. It should be noted that the "mass per unit area of the positive electrode active material layer" refers to the mass per unit area of one positive electrode active material layer. For example, when the positive electrode has a positive electrode substrate and positive electrode active material layers are respectively provided on both sides of the positive electrode substrate, the "mass per unit area of the positive electrode active material layer" is the mass per unit area of the positive electrode active material layer on one side.
[0047] (negative electrode)
[0048] The negative electrode comprises a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The structure of the intermediate layer is not particularly limited, and can be selected from the structures exemplified in the above-mentioned positive electrode.
[0049] The negative electrode substrate has conductivity. As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel, aluminum, or their alloys, carbonaceous materials, etc. can be used. Among them, copper or copper alloys are preferred. As the negative electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the perspective of cost, foil is preferred. Therefore, as the negative electrode substrate, copper foil or copper alloy foil is preferred. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be cited.
[0050] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate to the above range, the strength of the negative electrode substrate can be increased, and the energy density per unit volume of the secondary battery can be increased.
[0051] The negative electrode active material layer contains a negative electrode active material and may contain any component such as a conductive agent, a binder, a thickener, and a filler as required.
[0052] The negative electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, W as ingredients other than the negative electrode active material, conductive agent, binder, thickener and filler.
[0053] The negative electrode active material can be appropriately selected from known negative electrode active materials. As the negative electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. Examples of negative electrode active materials include: metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxides, Ti oxides, and Sn oxides; Li 4 Ti 5 O 12 、LiTiO 2 、TiNb 2 O 7 Titanium-containing oxides such as silicon carbide; polyphosphate compounds; silicon carbide; carbon materials such as graphite and non-graphite carbon (graphitizable carbon or non-graphitizable carbon). Among these materials, graphite and non-graphite carbon are preferred, and graphite is more preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.
[0054] “Graphite” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before charge / discharge or in the discharged state. 002 ) is a carbon material having a diameter of 0.33 nm or more and less than 0.34 nm. As graphite, natural graphite and artificial graphite can be cited. From the viewpoint of obtaining a material with stable physical properties, artificial graphite is preferred. From the viewpoint of high crystallinity, larger discharge capacity per unit mass of the negative electrode active material, and larger initial input, natural graphite is preferred.
[0055] “Non-graphite carbon” refers to the average lattice spacing (d ) of the (002) plane determined by X-ray diffraction before charge / discharge or in the discharged state. 002 ) is a carbon material having a carbon thickness of 0.34 nm to 0.42 nm. Examples of non-graphite carbon include difficult-graphitization carbon and easy-graphitization carbon. Examples of non-graphite carbon include materials derived from resins, petroleum asphalt or materials derived from petroleum asphalt, petroleum coke or materials derived from petroleum coke, materials derived from plants, materials derived from alcohols, and the like.
[0056] Here, the "discharge state" refers to a state in which the carbon material as the negative electrode active material is discharged in a manner that the lithium ions that can be stored and released are fully released along with the charge and discharge. For example, the following state: in a half-cell using the negative electrode containing the carbon material as the negative electrode active material as the working electrode and the metal Li as the counter electrode, the open circuit voltage is 0.6V or more.
[0057] "Difficult to graphitize carbon" refers to the above-mentioned 002 It is a carbon material with a diameter of 0.36nm to 0.42nm.
[0058] "Easily graphitizable carbon" refers to the above-mentioned 002A carbon material having a diameter of 0.34 nm or more and less than 0.36 nm.
[0059] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be set to 1 nm to 100 μm, for example. When the negative electrode active material is a carbon material, a titanium-containing oxide or a polyphosphate compound, its average particle size can be 1 μm to 100 μm. When the negative electrode active material is Si, Sn, Si oxide or Sn oxide, etc., its average particle size can be 1 nm to 1 μm. By making the average particle size of the negative electrode active material above the above lower limit, the manufacture or handling of the negative electrode active material becomes easy. By making the average particle size of the negative electrode active material below the above upper limit, the electronic conductivity of the negative electrode active material layer is improved. In order to obtain a powder with a specified particle size, a pulverizer, a classifier, etc. can be used. The pulverization method and the classification method can be selected from the methods exemplified in the above-mentioned positive electrode, for example. When the negative electrode active material is a metal such as metal Li, the negative electrode active material layer can be in the form of a foil.
[0060] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% to 99.5% by mass, more preferably 90% to 99% by mass. When the content of the negative electrode active material is within the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.
[0061] The conductive agent, binder, thickener, filler and the like as optional components in the negative electrode active material layer can be selected from the materials exemplified in the positive electrode described above.
[0062] The content of the conductive agent in the negative electrode active material layer may be 3% by mass or less or 1% by mass or less, and the negative electrode active material layer may not contain the conductive agent.
[0063] The content of the binder in the negative electrode active material layer is preferably 0.5% by mass to 5% by mass, and more preferably 0.8% by mass to 3% by mass.
[0064] The content of the thickener in the negative electrode active material layer is, for example, preferably 0.1% by mass to 6% by mass, and more preferably 0.5% by mass to 3% by mass.
[0065] The content of the filler in the negative electrode active material layer may be, for example, 0.1% to 8% by mass, or 0.5% to 5% by mass. The content of the filler in the negative electrode active material layer may be 3% by mass or less, or 1% by mass or less, or the negative electrode active material layer may not contain any filler.
[0066] The mass per unit area of the negative electrode active material layer is 3.8 mg / cm 2 ~4.8mg / cm 2The lower limit of the mass per unit area of the negative electrode active material layer is preferably 4.0 mg / cm 2 , more preferably 4.1 mg / cm 2 or 4.2 mg / cm 2 By making the mass per unit area of the negative electrode active material layer greater than the above lower limit, the input retention rate after storage in a high temperature environment can be further improved. The upper limit of the mass per unit area of the negative electrode active material layer is preferably 4.7 mg / cm 2 or 4.6 mg / cm 2 , and sometimes more preferably 4.4 mg / cm 2 , 4.3mg / cm 2 , 4.2mg / cm 2 or 4.1 mg / cm 2 . By making the mass per unit area of the negative electrode active material layer below the above upper limit, the initial input becomes larger. In addition, by making the mass per unit area of the negative electrode active material layer below the above upper limit, the input maintenance rate after storage in a high temperature environment also tends to be improved. The mass per unit area of the negative electrode active material layer can be adjusted by the coating amount per unit area of the negative electrode mixture paste when forming the negative electrode active material layer, etc.
[0067] The lower limit of the average thickness of the negative electrode active material layer is 30 μm, preferably 32 μm, and more preferably 34 μm. By making the average thickness of the negative electrode active material layer above the above lower limit, the input maintenance rate after storage in a high temperature environment can be further improved. As the upper limit of the average thickness of the negative electrode active material layer, it is preferably 50 μm, more preferably 45 μm, and sometimes more preferably 42 μm, 40 μm, 38 μm, 36 μm or 34 μm. By making the average thickness of the negative electrode active material layer below the above upper limit, the initial input becomes larger. In addition, by making the average thickness of the negative electrode active material layer below the above upper limit, the input maintenance rate after storage in a high temperature environment also tends to increase. The average thickness of the negative electrode active material layer can be within the range of any of the above lower limits to any of the above upper limits.
[0068] The porosity of the negative electrode active material layer can be, for example, 30% to 60%. As the lower limit of the porosity, it is preferably 35%, more preferably 38%, further preferably 40%, and further preferably 42%, 44% or 46%. By making the porosity of the negative electrode active material layer above the above lower limit, the initial input of the non-aqueous electrolyte storage element becomes larger, and the input maintenance rate after storage in a high temperature environment is further improved. On the other hand, as the upper limit of the above porosity, it is preferably 55%, more preferably 50%, and sometimes further preferably 48%. By making the porosity of the negative electrode active material layer below the above upper limit, there is a tendency for the initial input of the non-aqueous electrolyte storage element to become larger. The porosity of the negative electrode active material layer can be adjusted by the particle size of the negative electrode active material, whether or not compression is performed during manufacturing, and the pressure of compression.
[0069] (Relationship between Positive Electrode Active Material Layer and Negative Electrode Active Material Layer)
[0070] The lower limit of the ratio of the mass per unit area of the negative electrode active material layer to the mass per unit area of the tungsten element contained in the positive electrode active material layer is preferably 30, and sometimes more preferably 32, 34, 36, 40 or 50. By making the ratio above the above lower limit, there is a tendency to further improve the input maintenance rate after storage in a high temperature environment. On the other hand, as the upper limit of the ratio, it is preferably 70, and sometimes more preferably 60, 50, 45 or 42. By making the ratio below the above upper limit, there is a tendency for the initial input to become further larger. The ratio can be within the range of any of the above lower limits to any of the above upper limits.
[0071] The ratio of the mass per unit area of the negative electrode active material layer to the mass per unit area of the tungsten element contained in the positive electrode active material layer can be adjusted by the content of the tungsten element in the positive electrode active material, the mass per unit area of the positive electrode active material layer and the negative electrode active material layer (coating mass), etc.
[0072] (Isolator)
[0073] The separator can be appropriately selected from known separators. As the separator, for example, a separator consisting only of a substrate layer, a separator having a heat-resistant layer containing heat-resistant particles and an adhesive formed on one or both surfaces of the substrate layer, etc. can be used. As the shape of the substrate layer of the separator, for example, woven fabrics, non-woven fabrics, porous resin films, etc. can be cited. Among these shapes, porous resin films are preferred from the viewpoint of strength, and non-woven fabrics are preferred from the viewpoint of liquid retention of non-aqueous electrolytes. As the material of the substrate layer of the separator, from the viewpoint of the shutdown function, for example, polyolefins such as polyethylene and polypropylene are preferred, and from the viewpoint of resistance to oxidative decomposition, for example, polyimides, aromatic polyamides, etc. are preferred. As the substrate layer of the separator, a material composited with these resins can be used.
[0074] The heat-resistant particles contained in the heat-resistant layer preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 500°C in an air atmosphere of 1 atmosphere, and more preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 800°C. As materials whose mass reduction is less than the prescribed value, inorganic compounds can be cited. As inorganic compounds, for example, oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminum silicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate; covalently bonded crystals such as silicon and diamond; talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, and other mineral resources or their artificial products. As inorganic compounds, monomers or composites of these substances can be used alone, or two or more can be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of safety of the electric storage element.
[0075] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, the "porosity" is a value based on volume, and refers to a value measured by a mercury porosimeter.
[0076] As a separator, a polymer gel composed of a polymer and a non-aqueous electrolyte can be used. As polymers, for example, polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyvinylidene fluoride, etc. can be cited. When a polymer gel is used, there is an effect of suppressing leakage. As a separator, a porous resin film or non-woven fabric as described above can be used together with a polymer gel.
[0077] (Non-aqueous electrolyte)
[0078] The non-aqueous electrolyte can be appropriately selected from known non-aqueous electrolytes. A non-aqueous electrolyte can be a non-aqueous electrolyte solution. The non-aqueous electrolyte solution contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.
[0079] As nonaqueous solvent, can suitably select from known nonaqueous solvent.As nonaqueous solvent, can enumerate cyclic carbonate, linear carbonate, carboxylate, phosphoric acid ester, sulfonic acid ester, ether, amides, nitrile etc.As nonaqueous solvent, can use the nonaqueous solvent that a part of the hydrogen atom that comprises in these compounds is replaced by halogen.
[0080] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among them, EC is preferred.
[0081] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among them, EMC is preferred.
[0082] As non-aqueous solvent, preferably use cyclic carbonate or chain carbonate, more preferably use cyclic carbonate and chain carbonate.By using cyclic carbonate, can promote the dissociation of electrolyte salt, improve the ion conductivity of non-aqueous electrolyte.By using chain carbonate, can suppress the viscosity of non-aqueous electrolyte to be low.When using cyclic carbonate and chain carbonate, as the volume ratio of cyclic carbonate and chain carbonate (cyclic carbonate: chain carbonate), for example, preferably set to the range of from 5:95 to 50:50.
[0083] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, Among them, lithium salts are preferred.
[0084] As lithium salt, LiPF 6 、LiPO 2 F 2 , LiBF 4 、LiClO 4 、LiN(SO 2 F) 2 Inorganic lithium salts, such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), lithium bis(oxalate)difluorophosphate (LiFOP), etc., lithium oxalate salts, LiSO 3 CF 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiN(SO 2 CF 3 )(SO 2 C 4 F 9 )、LiC(SO2 CF 3 ) 3 、LiC(SO 2 C 2 F 5 ) 3 Among them, inorganic lithium salts are preferred, and LiPF 6 .
[0085] When the non-aqueous electrolyte contains LiPF 6 When LiPF 6 It is easy to react with the trace amount of water in the non-aqueous electrolyte to generate HF. It is believed that the presence of HF in the non-aqueous electrolyte promotes the dissolution of tungsten from the positive electrode active material into the non-aqueous electrolyte. In addition, when LiPO 2 F 2 When an electrolyte salt having anions containing fluorine, oxygen and phosphorus, such as lithium bis(oxalate)difluorophosphate (LiFOP), is used, it is believed that the dissolution of tungsten from the positive electrode active material into the non-aqueous electrolyte is further promoted. Therefore, when a non-aqueous electrolyte storage element using a non-aqueous electrolyte containing such a component is used as an embodiment of the present invention, the effect of increasing the input after storage in a high temperature environment is particularly significant. The content of the electrolyte salt having anions containing fluorine, oxygen and phosphorus in the non-aqueous electrolyte at 20°C and 1 atmosphere can be, for example, 0.01 mol / dm 3 ~0.5mol / dm 3 , which can be 0.03 mol / dm 3 ~0.3mol / dm 3 , or 0.05 mol / dm 3 ~0.2mol / dm 3 .
[0086] The content of the electrolyte salt in the non-aqueous electrolyte is preferably 0.1 mol / dm 3 ~2.5mol / dm 3 , more preferably 0.3 mol / dm 3 ~2.0mol / dm 3 , more preferably 0.5 mol / dm 3 ~1.7mol / dm 3 , particularly preferably 0.7 mol / dm 3 ~1.5mol / dm 3 By setting the content of the electrolyte salt to be within the above range, the ion conductivity of the non-aqueous electrolyte can be improved.
[0087] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of the additives include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partial hydride of terphenyl, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, and citraconic anhydride. anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; vinyl sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, vinyl sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, bipyridine Disulfide, 1,3-propylene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, tetrakis(trimethylsilyl)titanate, etc. These additives may be used alone or in combination of two or more.
[0088] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% to 10% by mass, more preferably 0.1% to 7% by mass, further preferably 0.2% to 5% by mass, and particularly preferably 0.3% to 3% by mass, relative to the overall mass of the non-aqueous electrolyte. By making the content of the additive within the above range, the capacity retention performance or cycle performance after high temperature storage can be improved, or the safety can be further improved.
[0089] A solid electrolyte may be used as the non-aqueous electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.
[0090] The solid electrolyte can be selected from any material that has ion conductivity and is solid at room temperature (e.g., 15° C. to 25° C.), such as lithium, sodium, and calcium. Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and polymer solid electrolytes.
[0091] In the case of a lithium ion secondary battery, examples of the sulfide solid electrolyte include Li 2 S-P 2 S 5, LiI-Li 2 S-P 2 S 5 , Li 10 Ge-P 2 S 12 wait.
[0092] The shape of the nonaqueous electrolyte storage element of the present embodiment is not particularly limited, and examples thereof include cylindrical batteries, square batteries, flat batteries, coin batteries, button batteries, and the like.
[0093] Figure 1 1 shows a non-aqueous electrolyte storage element 1 as an example of a square battery. It should be noted that this figure is a perspective view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a square container 3. The positive electrode is electrically connected to a positive terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative terminal 5 via a negative electrode lead 51.
[0094] <Electricity storage device>
[0095] The non-aqueous electrolyte storage element of the present embodiment can be used as a storage unit (battery module) composed of a plurality of non-aqueous electrolyte storage elements as a power source for automobiles such as electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), a power source for electronic devices such as personal computers and communication terminals, or a power source for power storage, etc. In this case, it is sufficient to apply the technology of the present invention to at least one non-aqueous electrolyte storage element included in the storage unit.
[0096] Figure 2 An example of an electricity storage device 30 is shown in which an electricity storage unit 20 formed by collecting two or more electrically connected non-aqueous electrolyte storage elements 1 is further collected. The electricity storage device 30 may also include a bus bar (not shown) that electrically connects the two or more non-aqueous electrolyte storage elements 1, a bus bar (not shown) that electrically connects the two or more electricity storage units 20, etc. The electricity storage unit 20 or the electricity storage device 30 may also include a state monitoring device (not shown) that monitors the state of one or more non-aqueous electrolyte storage elements.
[0097] <Method for producing non-aqueous electrolyte storage element>
[0098] The manufacturing method of the non-aqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The manufacturing method, for example, comprises: a step of preparing an electrode body, a step of preparing a non-aqueous electrolyte, and a step of accommodating the electrode body and the non-aqueous electrolyte in a container. The step of preparing the electrode body comprises: a step of preparing a positive electrode and a negative electrode, and a step of forming an electrode body by stacking or winding the positive electrode and the negative electrode via a separator.
[0099] The step of preparing the positive electrode can be performed, for example, by applying a positive electrode mixture paste directly or via an intermediate layer on the positive electrode substrate and drying it. The positive electrode mixture paste contains various components constituting the positive electrode active material layer such as a positive electrode active material and a dispersion medium. The applied positive electrode mixture paste can also be dried and then pressed.
[0100] The step of preparing the negative electrode can be performed, for example, by applying a negative electrode mixture paste directly or via an intermediate layer on the negative electrode substrate and drying it. The negative electrode mixture paste contains various components constituting the negative electrode active material layer, such as a negative electrode active material, and a dispersion medium. The applied negative electrode mixture paste can also be pressed after drying. The porosity of the formed negative electrode active material layer can be adjusted by the presence or absence of the pressing and the pressing pressure.
[0101] The step of storing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte is used, the non-aqueous electrolyte can be injected from an injection port formed in the container and then the injection port can be sealed.
[0102] <Other embodiments>
[0103] It should be noted that the nonaqueous electrolyte storage element of the present invention is not limited to the above-mentioned embodiment, and various changes can be made within the scope of the main purpose of the present invention. For example, the structure of other embodiments can be added to the structure of a certain embodiment, and in addition, a part of the structure of a certain embodiment can be replaced with the structure of other embodiments or known technology. Furthermore, a part of the structure of a certain embodiment can be deleted. In addition, known technology can be added to the structure of a certain embodiment.
[0104] In the above embodiment, the non-aqueous electrolyte storage element is used as a rechargeable non-aqueous electrolyte secondary battery (lithium ion secondary battery), but the type, shape, size, capacity, etc. of the non-aqueous electrolyte storage element are arbitrary. The present invention can also be applied to capacitors such as various secondary batteries, double-layer capacitors or lithium ion capacitors.
[0105] In the above embodiment, the electrode body is described as a stacked positive electrode and a negative electrode with a separator interposed therebetween, but the electrode body may not have a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state where a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode.
[0106] Example
[0107] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples.
[0108] [Example 1]
[0109] (Production of positive electrode)
[0110] Preparation of LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O 2 A positive electrode active material having tungsten oxide attached to the surface of particles. The content of tungsten element in the positive electrode active material relative to transition metal elements other than tungsten element is 1 mol %.
[0111] The positive electrode mixture paste is prepared using the above-mentioned positive electrode active material, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. It should be noted that the mass ratio of the positive electrode active material, AB, and PVDF is 93:5:2 (solid content conversion). The coating mass (solid content mass) of 7.2 mg / cm2 was applied on both sides of the aluminum foil as the positive electrode substrate. 2 The positive electrode mixture paste is applied in a manner of , and dried. Then, roll pressing is performed to obtain a positive electrode having positive electrode active material layers stacked on both sides of the positive electrode substrate.
[0112] (Production of negative electrode)
[0113] The negative electrode mixture paste was prepared using graphite as the negative electrode active material, styrene-butadiene rubber (SBR) as the binder, carboxymethyl cellulose (CMC) as the thickener, and water as the dispersion medium. It should be noted that the mass ratio of graphite, SBR, and CMC was 98.5:1:0.5 (solid content conversion). The coating mass (solid content mass) of 4.42 mg / cm was applied to both sides of the copper foil as the negative electrode substrate. 2 The negative electrode mixture paste was applied in a manner and dried. Then, roll pressing was performed to obtain a negative electrode having negative electrode active material layers laminated on both sides of the negative electrode substrate. The mass per unit area of the negative electrode active material layer (i.e., the coating mass) was 4.42 mg / cm 2 The average thickness was 37 μm, the porosity was 46%, and the ratio of the mass per unit area of the negative electrode active material layer to the mass per unit area of the tungsten element contained in the positive electrode active material layer was 37.
[0114] (Non-aqueous electrolyte)
[0115] In a solvent prepared by mixing ethylene carbonate and ethyl methyl carbonate at a volume ratio of 30:70, 1.2 mol / dm 3 The concentration of dissolved LiPF 6 and dissolving LiPO at a concentration of 1.0 mass % 2 F 2 , and obtain a non-aqueous electrolyte.
[0116] (Isolator)
[0117] A polyolefin microporous film was used as the separator.
[0118] (Assembly of non-aqueous electrolyte storage element)
[0119] The positive electrode, negative electrode and separator were used to obtain a wound electrode body. The electrode body was placed in a container, a nonaqueous electrolyte solution was injected and the container was sealed to obtain a nonaqueous electrolyte storage device of Example 1.
[0120] [Examples 2 to 8, Comparative Examples 1 to 9]
[0121] The type of positive electrode active material, the mass per unit area, average thickness and porosity of the negative electrode active material layer, and the ratio of the mass per unit area of the negative electrode active material layer to the mass per unit area of the tungsten element contained in the positive electrode active material layer (ratio (negative electrode / W)) are as described in Tables 1 to 3. In addition, each nonaqueous electrolyte storage element of Examples 2 to 8 and Comparative Examples 1 to 9 was obtained in the same manner as in Example 1. The ratio (negative electrode / W) was adjusted by adjusting the mass per unit area (coating mass) of the positive electrode active material layer and the negative electrode active material layer.
[0122] In the column “Whether the positive electrode active material contains W (tungsten element)” in Tables 1 to 3, “Yes” indicates the positive electrode active material used in Example 1, and “No” indicates LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O 2 The average thickness and porosity of the negative electrode active material layer were adjusted by changing the coating mass (mass per unit area of the negative electrode active material layer) and the pressure during pressing. In addition, Example 2 is described in Tables 1 to 3, respectively.
[0123] [evaluate]
[0124] (1-1) Initial charge and discharge
[0125] For each non-aqueous electrolyte storage element obtained, initial charge and discharge were performed under the following conditions. In a constant temperature chamber at 25°C, constant current charging was performed with a charging current of 1.0C and a charge end voltage of 4.10V, and then constant voltage charging was performed at 4.10V. The end condition of charging was set to a total charging time of 3 hours. Then, a rest period of 10 minutes was set. Constant current discharge was performed with a discharge current of 1.0C and a discharge end voltage of 3.0V.
[0126] (1-2) Determination of initial input
[0127] For each non-aqueous electrolyte storage element after the initial charge and discharge, constant current charging was performed at a charging current of 1.0C in a thermostatic chamber at 25°C, adjusted to SOC50%, and stored in a thermostatic chamber at -30°C for 4 hours, and then charged at a constant current of 5C, 10C, 15C, 20C or 25C for 10 seconds respectively. After each charge was completed, constant current discharge was performed at a current of 1.0C to make the SOC 50%. After each charge was completed, constant current discharge was performed at a current of 1.0C to make the SOC 50%. The resistance value was calculated from the slope of the current during each charge and the voltage 1 second after the start of charging, and "{the difference between the voltage before charging and the upper limit voltage (4.3V)} / resistance value×upper limit voltage (4.3V)" was calculated as the initial input. It should be noted that input refers to the energy (power) that can be absorbed per unit time.
[0128] (1-3) Determination of input maintenance rate after storage in high temperature environment
[0129] Next, for each non-aqueous electrolyte storage element, constant current and constant voltage charging is performed at a charging current of 1.0C in a thermostatic chamber at 25°C to make the SOC 80%. Each non-aqueous electrolyte storage element is stored in a thermostatic chamber at 80°C for 10 days at this SOC 80%. Then, it is stored in a thermostatic chamber at 25°C for more than 3 hours, and constant current discharge is performed with a discharge current of 1.0C and a discharge end voltage of 3.0V. Then, the input is calculated by the same method as the initial input as described above, as the input after storage. The percentage of the input after storage relative to the initial input is calculated as the input maintenance rate (input maintenance rate after storage in a high temperature environment).
[0130] Tables 1 to 3 show the initial input and input maintenance rate of each nonaqueous electrolyte storage element.
[0131]
[0132]
[0133]
[0134] As shown in Table 1, the initial input of each nonaqueous electrolyte storage device of Comparative Examples 5 to 8 in which the positive electrode active material does not contain tungsten is small. The positive electrode active material contains tungsten and the mass per unit area of the negative electrode active material layer is less than 3.8 mg / cm 2 The nonaqueous electrolyte storage devices of Comparative Examples 2 to 4 have a large initial input, but a low input retention rate. The positive electrode active material contains tungsten and the mass per unit area of the negative electrode active material layer exceeds 4.8 mg / cm 2 The initial input of the non-aqueous electrolyte storage element of Comparative Example 1 is slightly smaller, and the input retention rate is low. In contrast, the positive electrode active material contains tungsten and the mass per unit area of the negative electrode active material layer is 3.8 mg / cm2 ~4.8mg / cm 2 , and the average thickness of the negative electrode active material layer is 30μm or more, the initial input of each non-aqueous electrolyte storage element of Examples 1 to 3 is as large as 118W or more, and the input maintenance rate is also as high as 81.0% or more. In addition, as shown in Tables 2 and 3, it can be seen that by increasing the porosity of the negative electrode active material layer and the ratio of the mass per unit area of the negative electrode active material layer to the mass per unit area of the tungsten element contained in the positive electrode active material layer, the input maintenance rate is further improved. It should be noted that, as shown in Table 1, the input maintenance rate of each non-aqueous electrolyte storage element of Comparative Examples 5 to 8 in which the positive electrode active material does not contain tungsten element increases as the mass per unit area of the negative electrode active material layer decreases. In contrast, for each non-aqueous electrolyte storage element of Examples 1 to 3 and Comparative Examples 1 to 3 in which the positive electrode active material contains tungsten element, the input maintenance rate shows a tendency to decrease when the mass per unit area of the negative electrode active material layer is too large or too small, and the mass per unit area of the negative electrode active material layer is 3.8mg / cm 2 ~4.8mg / cm 2 The input maintenance rate is high when the mass per unit area of the negative electrode active material layer is set to 3.8 mg / cm 2 ~4.8mg / cm 2 The effect of improving the input maintenance rate brought about by the range of is specifically exerted when the positive electrode active material contains tungsten element.
[0135] Industrial Applicability
[0136] The present invention can be applied to non-aqueous electrolyte storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles.
[0137] Explanation of symbols
[0138] 1 Non-aqueous electrolyte storage element
[0139] 2 Electrode body
[0140] 3 Container
[0141] 4 Positive terminal
[0142] 41 Positive wire
[0143] 5 Negative terminal
[0144] 51 Negative wire
[0145] 20 Storage Unit
[0146] 30Electrical storage device
Claims
1. A non-aqueous electrolyte storage element comprising: A positive electrode having a positive electrode active material layer, and a negative electrode having a negative electrode active material layer, The positive electrode active material layer includes a positive electrode active material containing tungsten element. The mass per unit area of the negative electrode active material layer is 3.8 mg / cm 2 ~4.8mg / 2 cm, The average thickness of the negative electrode active material layer is greater than or equal to 30 μm.
2. The nonaqueous electrolyte storage element according to claim 1, wherein The ratio of the mass per unit area of the negative electrode active material layer to the mass per unit area of the tungsten element contained in the positive electrode active material layer is 30 or more.
3. The nonaqueous electrolyte storage element according to claim 1 or 2, wherein: The porosity of the negative electrode active material layer is greater than 40%.
Citation Information
Patent Citations
Positive electrode material for lithium secondary battery, positive electrode and lithium secondary battery
JP2001006676A